The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7335773 ZenodoArchiveConcept: 7335772 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7299806 10.5281/zenodo.7335773 10.53832/edtechhub.0165 2339240:LJTXPKUD 2405685:4NSU75DR 2405685:ABK6ZFI8 2405685:PFKAMFI6
Keywords: _r:AddedByZotZen

Teacher Continuous Professional Development in Tanzania: Lessons Learnt - Chachage, Kristeen; Thakrar, Jay (EdTech Hub, 2023)
This report shares the experience and learning from the activities carried out as part of the Government of Tanzania's efforts to operationalise its National Framework for Teacher Continuous Professional Development (TCPD), which shifts TCPD from discreet workshops to cost-effective, ongoing, school-based professional development. It is among the first of its kind at a national level, particularly in low- and middle-income country contexts. Through a collaborative and responsive approach of adaptive technical assistance and innovation, the EdTech Hub team supported Government of Tanzania partners in developing and implementing a technology-enhanced, school-based, national TCPD system. This report begins with an overview of the activities implemented and then consolidates reflection through nine lessons learnt that could help inform current and future thinking on the design, delivery, and funding of TCPD programming in Tanzania. The TCPD reflected in this report is specific to Tanzania's teaching and learning environment. While we recognise that environments can vary widely, even between countries with similar goals and objectives, the report also seeks to contribute to any current and future analyses that collate features of effective TCPD from around the world. Keywords: teacher professional development; teacher training; technology; learning management system; communities of learning; teacher needs assessment; An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7677950 ZenodoArchiveConcept: 7677949 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7677950 10.53832/edtechhub.0157 2339240:RBNTBT7Z 2405685:9WBV8KPN 2405685:EGL4QHDZ
Keywords: _r:AddedByZotZen

TCPD in Tanzania: Design-Based Implementation Research Cycle 1 Recommendations Policy Brief - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Frederick; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the first cycle of the DBIR carried out between September and December 2022. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; tanzania; communities of learning An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7948836 ZenodoArchiveConcept: 7948835 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7948836 10.53832/edtechhub.0166 2339240:N4CC2DD8 2405685:FICAJDR3 2405685:HUR5C9QN 2405685:XVCIV366
Keywords: _r:AddedByZotZen